PTH-068 The use of Oesophageal Capsule Endoscopy in Patients with Haemophilia; Experience from a Tertiary Centre. (4th June 2013) - Ang, Y L; Koulaouzidis, A; Douglas, S; Plevris, J N
Abstract : Introduction: A great proportion of haemophiliacs are considered at risk of being co-infected with hepatitis C (HCV) and variant Creutzfeldt-Jakob Disease (vCJD). 1 Chronic hepatitis C leads to liver cirrhosis, which in turn causes portal hypertension and varices. 2 Alternative endoscopic modalities have been developed for the investigation of the upper gastrointestinal (GI) tract, such as oesophageal capsule endoscopy (OCE). However, OCE is widely accepted and its indications are still under evaluation. 3 Our aim was to evaluate the use of OCE in a tertiary referral centre for GI problems in Lothian, Southeast Scotland, giving a special focus on OCE in haemophiliacs. Methods: A retrospective review of the OCE database from May 2005 to March 2012. Electronic case notes and OCE reports were reviewed. Demographics and clinical background, in particular haemophilia, hepatitis C, HIV and cirrhosis, reason for referral and OCE findings were abstracted. Results: A total of 65 OCEs (50 patients; 27 M/23 F; mean age: 52.7 ± 13.7 years) were carried out in the aforementioned period. 32% pts had haemophilia (16/50 patients/all male; mean age: 51.6 ± 9.8 years; range 31–78 years; 28 OCEs); 5 pts had repeat OCEs (1 pt: 1 repeat, 2 pts: 2 repeat, 1 pt: 3 repeat & 1 patient: 4 repeat OCEs). All haemophiliacs were infected with HCV; 2 pts were co-infected with HIV. 3/16 (18.75%) of haemophiliacs had established cirrhosis, 5/16 (31.25%) probable cirrhosis. In haemophiliacs, indications for OCE were: variceal surveillance (OCEs group A: 17/28; 60.7%) and/or other upper GI symptoms (OCEs group B: 11/28; 39.3%). PillCam®ESO1 was used in 15/28 (53.6%) occasions and PillCam®ESO2 for the rest (13/28; 46.4%). The overall diagnostic yield (DY) of OCE in haemophiliacs was 78% (21/28). The DY was similar in OCEs group A: 64.7% (findings in 11/17) and OCEs group B: 54.5% (findings in 6/11 ), P = 1.0. Oesophageal transit times were mean: 166s; range: 3–1171s. All capsules reached the stomach, but only 8/28 (28.5%) capsules entered the duodenum. Conclusion: OCE is a useful and acceptable alternative to conventional endoscopy in selected groups of patients. In particular, OCE in haemophiliacs has a high DY and should be considered a first line investigation to guide further endoscopic intervention. Disclosure of Interest: None Declared. References: Meijer K, et a l. HCV-related liver cancer in people with haemophilia. Haemophilia 2012; 18:17–24 de Franchis R. Non-invasive (and minimally invasive) diagnosis of oesophageal varices. J Hepatol 2008; 49:520–7 Guturu P, et al . Capsule endoscopy with PILLCAM ESO for detecting esophageal varices: a meta-analysis. Minerva Gastroenterol Dietol 2011; 57:1–11